Magnetic resonance quantification of skeletal muscle lipid infiltration in a humanized mouse model of Duchenne muscular dystrophy. (29th November 2022) - Khattri, Ram B.; Batra, Abhinandan; Matheny, Michael; Hart, Cora; Henley‐Beasley, Spencer C.; Hammers, David; Zeng, Huadong; White, Zoe; Ryan, Terence E.; Barton, Elisabeth; Bernatchez, Pascal; Walter, Glenn A.
Abstract: Rodent models of Duchenne muscular dystrophy (DMD) often do not recapitulate the severity of muscle wasting and resultant fibro‐fatty infiltration observed in DMD patients. Having recently documented severe muscle wasting and fatty deposition in two preclinical models of muscular dystrophy (Dysferlin‐null and mdx mice) through apolipoprotein E ( ApoE ) gene deletion without and with cholesterol‐, triglyceride‐rich Western diet supplementation, we sought to determine whether magnetic resonance imaging and spectroscopy (MRI and MRS, respectively) could be used to detect, characterize, and compare lipid deposition in mdx ‐ ApoE knockout with mdx mice in a diet‐dependent manner. MRI revealed that both mdx and mdx ‐ ApoE mice exhibited elevated proton relaxation time constants (T2 ) in their lower hindlimbs irrespective of diet, indicating both chronic muscle damage and fatty tissue deposition. The mdx‐ApoE mice on a Western diet ( mdx‐ApoE W ) presented with greatest fatty tissue infiltration in the posterior compartment of the hindlimb compared with other groups, as detected by MRI/MRS. High‐resolution magic angle spinning confirmed elevated lipid deposition in the posterior compartments of mdx ‐ ApoE W mice in vivo and ex vivo, respectively. In conclusion, the mdx‐ApoE W model recapitulates some of the extreme fatty tissue deposition observed clinically in DMD muscle but typically absent in mdx mice. This preclinical model will help facilitate the development of new imaging modalities directly relevant to the image contrast generated in DMD, and help to refine MR‐based biomarkers and their relationship to tissue structure and disease progression. Abstract : A new model of DMD mouse (the mdx and Apo‐lipoprotein E knock out) on different diet regime has been studied with both invasive and noninvasive magnetic resonance (MR) techniques. Both MR imaging and MR spectroscopy affirmed higher level of lipid infiltration on double knocked out mice on Western high‐fat diet ( mdx‐ApoE W ), similar to human condition. We believed that this mouse model on Western high‐fat diet opens up new avenues for validating MR biomarkers and therapeutic development.